The Expression of Tissue Factor and Tissue Factor Pathway Inhibitor in Aortic Smooth Muscle Cells Is Up-regulated in Synthetic Compared to Contractile Phenotype - Ghrib, Farida; Brisset, Anne-Cécile; Dupouy, Dominique; Terrisse, Anne-Dominique; Navarro, Chantal; Cadroy, Yves; Boneu, Bernard; Sié, Pierre (Thrombosis and Haemostasis, 2002)
Tissue factor (TF) and its specific inhibitor TF pathway inhibitor (TFPI) are produced by vascular smooth muscle cells (SMCs) in vitro and are increased in vivo in atherosclerotic compared to normal vessels. Besides local regulation of the hemostatic balance, this may be related to non-hemostatic TF/protease dependent functions such as SMC proliferation, adhesion and migration. The aim of the study was to compare the expression of both proteins between the contractile (normal adult) and synthetic (neo-intimal) SMC phenotypes.Primary cultures of SMCs isolated from rat thoracic aorta before and 10 days after balloon injury displayed stable characteristics of the contractile and synthetic phenotype, respectively. Synthetic SMCs expressed more TF mRNA than contractile SMCs, but released excess TF in the conditioned medium, so that the cell-associated TF activity measured by a factor Xa generating assay remained similar in the two subtypes. Accordingly, cell surface thrombogenicity measured under blood flow conditions was also similar. The production and release of functional TFPI was enhanced by a factor 3 to 6 (p < 0.01) in synthetic SMCs.A difference in the quantitative expression of TF and TFPI is a new distinctive feature of SMC phenotypes. Matrix-associated TFPI derived from synthetic SMCs may serve as an anchorage for their migration and regulate protease-activated processes during neo-intima formation.
Keywords: Tissue factor; smooth muscle cells; thrombosis